The Role of Macronutrients in Chronic Obstructive Pulmonary Disease: A Review - Kristy, Anastasia; Hardian, Harris; Putra, Wayan Wahyu Semara; Yaniswari, Ni Made Dwita; Tania, Tryna (Faculty of Medicine Universitas Airlangga, 2024)
The incidence of chronic obstructive pulmonary disease (COPD) is rising and is still regarded as one of the challenging medical issues. Regardless of the main relationship between tobacco smoking and toxic particle exposure with COPD, factors like nutritional status also play an important role in COPD progression and outcome, as the factor is an adaptable aspect. Malnutrition, sarcopenia, and obesity are nutritional problems that are often encountered in COPD patients. Macronutrients, namely carbohydrates, fat, and protein, support the adjunctive treatment options for COPD. The ideal dietary pattern includes low carbohydrates, medium fats preferably polyunsaturated fatty acids (PUFA), and high proteins to improve COPD symptoms, preserve muscle mass, and delay disease progression. High carbohydrate intake might also increase the respiratory quotient (RQ) which results in higher carbon dioxide (CO2) production and oxygen (O2) demand compared to fat and protein intake. Daily calorie intake should be adjusted to personal nutritional status. Higher calories in malnourished, sarcopenic patients and targeted weight loss in obese patients show improvements in lung function, frequency of exacerbations, and hospitalization rate. In obese individuals with COPD, however, maintaining a slightly higher body mass index (BMI) of 25-30 kg/m2 was associated with lower mortality. This literature review summarized the significant role of macronutrients in COPD patients and the practical approach to macronutrient intervention in individuals with different nutritional statuses.